2022
DOI: 10.1021/acscatal.1c04547
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the Role of B Site-Selective Doping of Aliovalent Cations on Enhancing Sacrificial Visible Light-Induced Photocatalytic H2 and O2 Evolution over BaTaO2N

Abstract: The doping of foreign cations and anions is one of the effective strategies for engineering defects and modulating the optical, electronic, and surface properties that directly govern the photocatalytic O 2 and H 2 evolution reactions. BaTaO 2 N (BTON) is a promising 600 nm-class photocatalyst because of its absorption of visible light up to 660 nm, small band gap (E g = 1.9 eV), appropriate valence band-edge position for oxygen evolution, good stability under light irradiation in concentrated alkaline solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 74 publications
1
47
0
Order By: Relevance
“…Next, the effect of Al 3+ -Mg 2+ (co)substitution at the Ta site in BaTaO 2 N on electronic band structures was studied by DFT-HSE12s. As shown in Figure 5, the estimated bandgap energy of pristine BaTaO 2 N is 1.49 eV (direct-type), which is slightly lower than the experimentally 32,55 and theoretically 56 by a significant decrease in the band gap with an increase in the Al content, which is beneficial to absorb a significant fraction of visible light. Among the three cosubstituted models, the BaTa 0.5 Al 0.375 Mg 0.125 O 2 N model has the narrowest band gap (1.36 eV).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 72%
See 3 more Smart Citations
“…Next, the effect of Al 3+ -Mg 2+ (co)substitution at the Ta site in BaTaO 2 N on electronic band structures was studied by DFT-HSE12s. As shown in Figure 5, the estimated bandgap energy of pristine BaTaO 2 N is 1.49 eV (direct-type), which is slightly lower than the experimentally 32,55 and theoretically 56 by a significant decrease in the band gap with an increase in the Al content, which is beneficial to absorb a significant fraction of visible light. Among the three cosubstituted models, the BaTa 0.5 Al 0.375 Mg 0.125 O 2 N model has the narrowest band gap (1.36 eV).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 72%
“…Apparently, the magnified XRD patterns indicate a slight alteration in the 2 angle position of the 110 reflection toward higher or lower 2 angles when Ta 5+ is partially substituted by Al 3+ (BTON2) or Mg 2+ (BTON3) in the octahedral coordination, indicating the lattice volume contraction or expansion, respectively. 32 As the ionic radius of Al 3+ is smaller than that of Ta 5+ , while the ionic radius of Mg 2+ is larger than that of Ta 5+ , the 2 angle position of the 110 reflections of the Al 3+ -Mg 2+ dual-substituted samples (BTON4-6) is near to that of pristine BaTaO 2 N (BTON1). Also, the concurrent substitution of smaller O 2-(126 pm) for larger N 3-(157 pm) to compensate charge balance in the Al 3+ -Mg 2+ dualsubstitution for Ta 5+ may have lessened the lattice expansion.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…They found that the experimental photocatalytic reaction rates were well described by using the adsorption energies of the reaction intermediates. 25 To the best of our knowledge, some basic questions about the properties of BaTaO 2 N surfaces are still unsolved, such as (i) detailed electronic properties have not been presented and the corresponding bonding mechanism has not been clearly understood; (ii) the optical properties have not been calculated, particularly in their anisotropic behavior; and (iii) the effect of exposed termination on photocatalysis-related properties has not been fully elucidated. Therefore, to solve these issues, we have carried out DFT calculations to determine the structures and surface energies of low-indexed surfaces of BaTaO 2 N by considering different terminations, to study their electronic and optical properties, to explore the adsorption of molecular and dissociated water on surfaces in detail, and to reveal the mechanisms of the HER and the OER.…”
Section: Introductionmentioning
confidence: 99%